Phrasal Verbs in George Orwell’s 1984 and Its Arabic Translation - Kulsum, Eva Meidi (e-Journal of Linguistics, 2020)
In English, phrasal verb comprises of a verb and a particle, so does in Arabic. Although both languages have phrasal verbs, it does not mean that each phrasal verb in English is translated in the same form as a phrasal verb into Arabic. This research aimed to know the translation shift of phrasal verbs in George Orwell’s novel entitled 1984 and its Arabic translations. This research employed a qualitative descriptive method using a purposive sampling technique. The result showed that Arabic is a rich vocabulary language. It was proven by more than 50% of the English phrasal verbs found in the novel is translated into Arabic in the same category or grammatical class, not in the form of description.